1221Baseline Global DNA Hypermethylation Increase the Risk of Cerebrovascular Disease Mortality in Japanese Population. (2nd September 2021) - Tsuboi, Yoshiki; Yamada, Hiroya; Munetsuna, Eiji; Fujii, Ryosuke; Yamazaki, Mirai; Ando, Yoshitaka; Mizuno, Genki; Ishikawa, Hiroaki; Ohashi, Koji; Maeda, Keisuke; Hashimoto, Shuji; Hamajima, Nobuyuki; et al.
Abstract: Background: DNA methylation plays an important role in progression of cardiovascular disease (CVD). The methylation status of long interspersed nuclear element-1 (LINE-1) reflects the global DNA methylation level and is associated with lipid profiles and glycemia. We conducted a longitudinal study to examine the association between LINE-1 DNA methylation and CVD mortality in a Japanese elderly population. Methods: We targeted for 357 subjects (143 men and 214 women) who were more than 60 years, participated in the health checkup in 1990, and had no clinical history of cancer, stroke, or ischemic heart disease. During 29 years of follow-up period, total 69 subjects were died from CVD, and died of cerebrovascular disease (CBD) and ischemic heart disease (IHD) were 25 and 13, respectively. LINE-1 DNA methylation was measured using PBMCs. We defined the hypermethylation group as greater than median of the LINE-1 DNA methylation levels and hypomethylation group as others. Multivariable Hazard ratios (HRs) for each disease mortality were calculated by the Cox proportional hazard model. We adjusted for age, sex, smoking habits, and alcohol consumption. Results: Significantly higher HRs for CVD and CBD mortality were observed in the hypermethylation group compared to the hypomethylation group (CVD: HR 1.67 [95%CI 1.02-2.73], CBD: HR 3.29 [95%CI 1.29-8.40]). However, IHD mortality did not associated with LINE-1 DNA methylation. Conclusions: We found that LINE-1 DNA hypermethylation in PBMCs was associated with high CVD mortality, especially CBD mortality. Key messages: Higher levels of LINE-1 methylation in PBMCs can be a predictive marker for CBD risk